Enhancing school performance through whole school intervention: a case study - Giri, Dhundi Raj; Neupane, Bharat Prasad; Dahal, Niroj; Subedi, Dhanapati (Frontiers in Education, 2025)
Whole School Intervention (WSI) is a school improvement approach that engages the entire school community to enhance various aspects of the school, addressing the needs of every child and ensuring opportunities for success. This study, grounded in the theory of complex adaptive systems, investigates the implementation of the WSI approach in a private school in Nepal to assess its impact on school improvement. The central research question is: How does WSI improve the school system? The study examines multiple areas for intervention by involving members of the entire school community through a qualitative case study methodology. Various data collection techniques, including participatory needs analysis, in-depth interviews, focus group discussions, and video recordings, were employed to understand the school context and the transformation occurring during the intervention, which was carried out in four phases. The findings indicate that WSI served as a practical approach to school improvement by transforming leadership capacity. It shifted traditional authoritative leadership to distributed, democratic, and participatory practices. Additionally, WSI nurtured a positive school culture and supported teacher professional development, thereby improving pedagogical knowledge and skills, which, in turn, enhanced student learning outcomes. The collective efforts of all school stakeholders also contributed to maintaining a conducive learning environment, exemplified through initiatives like school gardening. The article concludes by emphasizing that empowering participation and fostering a long-term shared vision are critical for the sustainability of overall school improvement.